Solar Enhanced Oil Recovery as the Solution to Enhance Oil and Gas Production for Mature Fields in Indonesia - Shafa Alifia Salsabila; Monika Putri Maharani; Ariyanti Putri Joestiawan (Purnomo Yusgiantoro Center, 2023)
Indonesia has a target of reducing 29% of GHG emissions by 2030 (NDC, 2022), reaching net-zero emissions in 2060 (LTS-LCCR, 2021), and obtaining 1 million BOPD oil production and 12 BSCFD gas production in 2030. Oil and gas companies have particular challenges to achieve the target in line with paying attention to national energy security despite the oil reserve and production declining since 1995 because of the maturity of the fields. In such a case, the enormous amount of remaining oil in place left by the primary and secondary production stages has led to the EOR method as the best way to improve oil production. In Indonesia's mature fields with specific reservoir conditions, steamflooding is currently a highly effective EOR method to increase oil production by 20–300% and reduce viscosity by up to 98%. However, the production of steam in huge quantities conventionally would require vast amounts of fossil fuel resources. Hence, replacing fossil fuel-derived steam with solar-derived steam would solve the twin problems of energy scarcity and greenhouse gas emissions. Solar EOR is a viable alternative to gas-fired steam production for the oil industry by using the sun's energy to generate steam. For designing the long-term Solar EOR, Ayman Solar Concentrator (ASC) technology on low-cost solar thermal energy storage will generate high-temperature steam for 24 hours all day by enabling the system to achieve higher temperatures with less mirror surface. The evaluation of annual energy output from the solar project's design could save more than 8,672,400 MMBTU/year of natural gas and cut the environmental footprint up to 1200 metric tonnes per day of net CO2 so that natural gas can be sold and allocated to various sectors. Furthermore, the economic analysis shows that solar EOR has the lowest operational. This technology's novelty is its low cost and ability to generate steam to supply it upon demand in Indonesia's ongoing steamflood project.